The Role of Islamic Educational Psychology in Improving The Quality of Learning - Mustakim, Mustakim; Sari, Dewi Purnama; Puspitasari, Rini (KOLABORASI: Journal of Multidisciplinary, 2024)
This study examines the role of Islamic educational psychology in improving the quality of learning through a qualitative library research approach. Data were collected from books, journal articles, and other relevant academic sources, then analyzed using descriptive qualitative content analysis with thematic categorization. The findings show that Islamic educational psychology contributes to learning quality through four interconnected dimensions: understanding student characteristics, developing effective learning strategies, strengthening learning motivation, and creating a conducive learning atmosphere. These dimensions demonstrate that quality learning in Islamic education is not limited to academic achievement, but also includes spiritual, moral, emotional, and social development. The study further indicates that educators who integrate psychological insight with Islamic values are better able to design responsive, meaningful, and holistic learning experiences. Therefore, Islamic educational psychology serves as an important conceptual and practical foundation for improving learning quality and fostering balanced student development in Islamic educational contexts across contemporary classrooms today.